In Pursuit of a Stable Stabilization Policy in Sweden. From the Gold Standard to Inflation Targeting and Beyond - Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2019)
In a historical perspective, the stabilization policy regime in Sweden is in a state of constant change, affected by economic crises, international impulses, domestic politics, and developments in macroeconomic theory. Economists have been deeply involved in this process. The current framework for monetary and fiscal policy, with an independent central bank focusing on inflation targeting, and a rule-based fiscal policy, is not the final stage of this process. Future crises will once again change the goals, the instruments, and the institutional framework. In a historical perspective, the rapid expansion of the financial system, with the accompanying accumulation of private debt and high rates of asset inflation, stands out as a likely cause behind the next crisis. The next crisis will be followed by yet another step in the perennial pursuit of a better stabilization policy.
Keywords: E12; E30; E60; G01; H63; N14; 330; Monetary policy; fiscal policy; gold standard; price-level targeting; inflation targeting; financial repression; the Riksbank; Sweden